Proteasome Inhibitors in Cancer Therapy and their Relation to Redox Regulation - ŞAHİN, ALİ; YILMAZ, BETÜL (BENTHAM SCIENCE PUBL LTD, 2018)
Redox homeostasis is important for the maintenance of cell survival. Under physiological conditions, redox system works in a balance and involves activation of many signaling molecules. Regulation of redox balance via signaling molecules is achieved by different pathways and proteasomal system is a key pathway in this process. Importance of proteasomal system on signaling pathways has been investigated for many years. In this direction, many proteasome targeting molecules have been developed. Some of them are already in the clinic for cancer treatment and some are still under investigation to highlight underlying mechanisms. Although there are many studies done, molecular mechanisms of proteasome inhibitors and related signaling pathways need more detailed explanations. This review aims to discuss redox status and proteasomal system related signaling pathways. In addition, cancer therapies targeting proteasomal system and their effects on redox-related pathways have been summarized.
Keywords: Proteasome inhibitors; redox status; signaling molecules; cancer therapy; redox homeostasis; proteasomal system; NF-KAPPA-B; PROTEIN-KINASE-C; CELL LUNG-CANCER; HEAT-SHOCK RESPONSE; RETINOBLASTOMA PROTEIN; IN-VITRO; TRANSCRIPTIONAL REGULATION; IRREVERSIBLE INHIBITOR; SELECTIVE INHIBITORS; SIGNAL-TRANSDUCTION